Kilka uwag o obowiązku udzielania przez lekarza podstawowej opieki zdrowotnej świadczeń poza zakresem swojej specjalizacji - Zoń, Katarzyna Maria (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
First it should be pointed out that a doctor has a duty to provide health services within the scope of his/her specialization. This basic rule arises from both statutory and deontological regulations.The aim of this paper is to analyze the issue of a primary care doctor duty to provide health services outside the scope of his/her specialization as an exception to the above rule. In this respect it is very significant to explain the statutory and deontological regulations related to this topic, because it is necessary for further considerations. Then the exceptions to the rule are discussed. In this context the specific duty to provide health services outside the scope of specialization, concerning a primary care doctor should be highlighted.In the end the conclusions of the analysis are presented.
Keywords: lekarze; podstawowa opieka medyczna; świadczenia zdrowotne; specjalizacja